Pengaruh Beban Kerja Dan Pengawasan Kerja Terhadap Lingkungan Kerja Pada Pt. Citra Hannochs Niagantara Medan - Julina Julina; Syawaluddin Syawaluddin; Mila Asmawiani Okta; Thomas Sumarsan Goh (STIE AMKOP, 2022)
PT. Citra Hannochs Niagaantara has the address at Jalan Attorney No. 5D, Medan which is engaged in selling Hannochs brand lamps. The company offers products such as: energy saving lamps, halogen, metal halide, LED lamps and various project lighting fixtures for civil works. The employee's workspace is considered to be still less comfortable for employees to carry out their work activities because employees feel that the workspace is too narrow so that employees are not free to work. Employees perceive that they accept many jobs at the same time. The process of implementing control within the company is considered to be still tight because in the company there are various systems and policies that must be obeyed by employees and some of these systems and policies make employees less comfortable at work. This research uses quantitative descriptive research. The total population in the study was 49 employees with a sampling technique using a saturated sample.Simultaneously there is a significant effect between the workload and work supervision variables on the work environment of PT. Citra Hannochs Niagantara. While partially found the workload variable has a significant effect on the work environment of employees of PT. Citra Hannochs Niagantara. Partially found work supervision variables have a significant effect on the work environment of employees of PT. Citra Hannochs Niagantara. The results of this study indicate that the work supervision variable has more influence than the workload on the work environment of the employees of PT. Citra Hannochs Niagantara. Keywords: Workload, Work Supervision, Work Environment